KELEKATAN (ATTACHMENT) ORANG TUA DALAM STIMULASI KEMANDIRIAN ANAK USIA DINI - Ayunda, Zahroh; Aulia , Annisa (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2022)
The quality of the relationship between children and parents is an important factor in the development of children. The role of the family does not only concern the fulfillment of all biological needs, but also psychological and sociological needs in the form of establishing a safe attachment between children and their parents. To realize this, the family rule system is expected to continue to encourage and color the behavior of children towards independence. The research and/or writing method used is literature review. The main references used are books, laws and regulations, seminar papers, printed and online editions of scientific journals, research results and scientific articles. The data analysis technique is descriptive argumentative. The results of the analysis show that high parental attachment to children is indicated by trust, being able to help, accepting children as they are, giving proper love and care to children. High quality can make individuals see themselves as worthy of love and view individuals in their social environment as reliable and able to think positively in living life so that independent behavior will appear in children.